Feeding Horses and Ponies - Mcbane, Susan (Ohio, USA David & Charles, 2003)
Clear, straghtforward advice on every aspect of feeding horses and poies for different requirments, with an informative problem-solving section which highlights a wide rang of feeding difficulties
"Includes extensive problem-solving section"
"Overcoming Common Feeding Problems"
12
Keywords: Animals; Horsemanship; Horses -- Breeding; Horses -- Training; Racing